INNOVATION OF ELECTRONIC-BASED TAX SERVICES IN INCREASING TAXPAYER PARTICIPATION - Kenni Arianti Putri (Inovasi, 2022)
One of the realistic steps taken by the Director General of Taxes is to provide tax services that make it easier for people to pay taxes. This principle is based on a thought about building awareness through an emotional approach. That the people as citizens need to be served well by the state, especially in terms of fulfilling their obligations. The state must be present as a facilitator who provides a sense of comfort and fun. This study aims to see the effect of electronic-based tax service innovation, especially in terms of reporting in an effort to increase taxpayer participation. Respondents in this study were private taxpayers who were in the tax office area of Central Jakarta, totaling 100 people. The data collection technique was carried out by giving primary questionnaires. In general, this study uses a positivism/quantitative approach with linear regression analysis. The results of the study indicate that there is a strong relationship between tax revenue and taxpayer participation with electronic tax reporting factors. This confirms that innovation in tax services is a technical factor that influences awareness of paying taxes.Keywords:        Electronic-Based Tax Innovation, E-SPT, Taxpayers, Awareness of Paying Taxes